Structured Continuous Objective-Based Assessment of Resident′s Performance at Point of Care (SCOPA) - Hijazi Mohammed (Annals of Saudi Medicine, 2005)
The assessment of the clinical performance of physicians-in-training is an important task. The critical care rotation is a mandatory rotation for most residency training programs and is designed to ensure the graduation of trainees who are able to initiate lifesaving management during medical emergencies. Ensuring that each resident fulfills the objectives of the rotation is of paramount importance. Unfortunately, the current assessment methods are subjective and suffer from many threats to validity and reliability that make the assessment inaccurate. In this review, the current assessment method is analyzed, and causes for inaccuracy are identified. A new model for assessment that is continuous, structured, objective-based and at the point of care (SCOPA) is proposed based on the best available assessment methods. Such a model might be useful for the assessment of trainee′s performance in critical care as well as non-critical care rotations.